IMPROVING STUDENTS’ READING COMPREHENSION THROUGH PREVIEW QUESTION READ SUMMARIZE AND TEST (PQRST) TECHNIQUE - Putri, Ima Rachmawati Sutrisna; Al Hakim, Luqman (UNIVERSITAS SLAMET RIYADI, 2018)
ABSTRACTThe research aims: (1) to find out whether PQRST technique can improve the students‟ reading comprehension at ninth grade student of SMP 27 Surakarta in the academic year of 2017/2018, and (2) to know how far the improvement students‟ of reading comprehension using PQRST at ninth grade of SMP 27 Surakarta in the academic year of 2017/2018. The researcher conducted a classroom action research at the ninth grade of SMP N 27 Surakarta from September up to October 2017. This research was conducted in class IX F which consisted of 27 students. The research concerned in improving students‟ reading comprehension on narrative texts using Preview Question Read Summarize and Test (PQRST) Technique. The research consisted of two cycles. The procedure of action research consisted of planning, implementation of the action, observation, and reflection. In collecting the data, the researcher used observation, interview and document. In analyzing the data, the researcher used quantitative and qualitative data analysis. The result of this research showed that Preview Question Read Summarize and Test (PQRST) Technique can improve students‟ reading comprehension on narrative texts at ninth grade of SMP N 27 Surakarta in the academic year of 2017/2018. The improvement can be seen from the result of the test. It was 65.8 in pre-test, then it became 72.6 in post-test 1 and it became higher in post-test 2 (82.8). From the result above, it can be concluded that Preview Question Read Summarize and Test (PQRST) Technique can improve students‟ reading comprehension on narrative texts at the ninth grade of SMP N 27 Surakarta. Keywords: Classroom Action Research, Preview Question Read Summarize Test (PQRST), Reading Comprehension. ABSTRAKPenelitian ini bertujuan: (1) untuk mengetahui apakah teknik PQRST dapat meningkatkan pemahaman membaca siswa pada siswa kelas sembilan SMP 27 Surakarta pada tahun akademik 2017/2018, dan (2) untuk mengetahui sejauh mana peningkatan peningkatan kemampuan siswa dalam membaca. pemahaman membaca menggunakan PQRST di kelas sembilan SMP 27 Surakarta pada tahun akademik 2017/2018. Peneliti melakukan penelitian tindakan kelas di kelas sembilan SMP N 27 Surakarta dari September hingga Oktober 2017. Penelitian ini dilakukan di kelas IX F yang terdiri dari 27 siswa. Penelitian ini berkaitan dengan meningkatkan pemahaman membaca siswa pada teks naratif menggunakan Teknik Preview Question Read Summarize and Test (PQRST). Penelitian ini terdiri dari dua siklus. Prosedur penelitian tindakan terdiri dari perencanaan, pelaksanaan tindakan, observasi, dan refleksi. Dalam mengumpulkan data, peneliti menggunakan observasi, wawancara dan dokumen. Dalam menganalisis data, peneliti menggunakan analisis data kuantitatif dan kualitatif. Hasil penelitian ini menunjukkan bahwa Teknik Preview Question Read Summarize and Test (PQRST) dapat meningkatkan pemahaman membaca siswa pada teks naratif di kelas sembilan SMP N 27 Surakarta pada tahun akademik 2017/2018. Peningkatan itu bisa dilihat dari hasil tes. Itu 65,8 di pre-test, kemudian menjadi 72,6 di post-test 1 dan itu menjadi lebih tinggi di post-test 2 (82,8). Dari hasil di atas, dapat disimpulkan bahwa Teknik Preview Question Read Summarize and Test (PQRST) dapat meningkatkan pemahaman membaca siswa pada teks naratif di kelas sembilan SMP N 27 Surakarta. Kata kunci: Penelitian Tindakan Kelas, Preview Pertanyaan Read Summarize Test (PQRST), Reading Comprehension.